The Cambridge dictionary of modern world history - Cook, Chris, 1945-; Stevenson, John, 1946- (Cambridge : Cambridge University Press, 2018)
In a world where we take for granted the ability to communicate instantly across vast distances and time, world history has come of age. We increasingly reflect on history from a position which no longer privileges Europe or the West, and from a global perspective which ranges from the Pacific Rim to the Balkans, and from Latin America to the Middle East. Compiled by an international team of contributors, area editors and general editors, The Cambridge Dictionary of Modern World History provides a much needed guide to the main global events, personalities and themes from the eighteenth century to the present. Major themes of war, politics, society and religion are covered, alongside more recent subjects within the discipline; from globalization and the environment to transnational social movements and human rights. This is an essential new work of reference not only for scholars and students but also for the wider general public.
Title from publisher's bibliographic system (viewed on 17 Nov 2017).
Keywords: History, Modern -- Dictionaries